Self-Mechanical Anal Dilatation: A Simple Trick to Minimize Postoperative Pain and Stenosis Following Hemorrhoidectomy With Radiofrequency - Eberspacher, Chiara; Mascagni, Pietro; Zeri, Kenneth Paul; Fralleone, Lisa; Naldini, Gabriele; Mascagni, Domenico (Frontiers in Surgery, 2021)
Aim: Hemorrhoidectomy is still the most effective surgical treatment for hemorrhoidal disease, but it is, however, associated with complications such as pain and stenosis. We proposed to break the “vicious circle” of “pain – sphincteric spasm – stenosis – pain” with the postoperative use of self-mechanical anal dilation. Methods: We retrospectively analyzed patients with hemorrhoidal disease presenting with a minimum of 3 quadrants piles, treated with radiofrequency hemorrhoidectomy between January 2018 and December 2019. All the patients that at 3 weeks presented sphincteric spasm with painful defecation, were considered. Thirty-nine patients performed the cycle of self-mechanical anal dilation (Group A). This group was 1:1 matched with homogeneous patients from our historical cohort of patients (Group B). Primary endpoint was the pain evaluation, secondary endpoints: WCS, patient’s overall satisfaction, anal sphincter spasm, scarring and the incidence of postoperative stenosis. Results: In Group A mean VAS was 3,25 after 14 days of application and 1,15 at the end. In Group B mean VAS was persistently higher, with a mean VAS of 5 (p = 0,000002) and 3,38 (p = 0,0000000000009). In Group A we observed an improvement of symptoms at the end of application, with a good overall satisfaction (Group A 7,4 vs Group B 5,9; p = 0,0000007) and a better mean WCS (Group A WCS 2,8 vs group B WCS 4,18; p = 0,0001). Stenosis was observed in 3/39 patients of Group B. Conclusions: Self-mechanical anal dilation improves the pain in late post-operative course, minimizing the risk of anal stenosis.